Stepping motion control for the Acrobot - Arrojado, Samiel Louie M.; Denoga, Gerald Jo C. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The Acrobot is a serial two-link planar mechanism with one passive joint between the ground and the first link and one actuated joint located between the two links. It has been a main focus of studies related to non-linear control and underactuated systems because of its complex behavior despite the simplicity of its configuration. Even though most studies based on the Acrobot focus on the swing-up problem, a number of developments have applied different modes of locomotion to the configuration. In this work, modified the Acrobot configuration and a generated control trajectory were developed to enable the Acrobot to execute stepping locomotion. The first link of the Acrobot was extended beyond the actuated joint to acts as legs that alternate in utility between each step. The input trajectory for the Acrobot was generated using a heuristic search algorithm, where distinct points in the trajectory were modified to minimize certain cost functions in order to achieve the stepping motion. A physical setup was fabricated to validate the generated trajectory for the Acrobot's stepping motion. The trajectory was applied to the physical setup and enforced with full state feedback from additional sensors that were placed to monitor the angles and velocities of both links throughout the motion. The results of the test using the physical setup indicate that stepping motion can be accomplished successfully for the Acrobot. This opens up opportunities to develop more complex control schemes to enable stepping in varying initial configurations other than flat ground. Coupled with the simplicity of the mechanism, the stepping Acrobot becomes a worthy candidate as a mode of locomotion in uneven terrain.
Thesis (M.S. Mechanical Engineering)--University of the Philippines Diliman
Keywords: Robots -- Control systems